The University Teacher role in the Magistery degree Practicum at Infantil and Primary Education - Marta Liesa Orús (Revista Electrónica Interuniversitaria de Formación del Profesorado)
This article shows the conclusions of an investigation plan which was showed in the Human Sciences Facultity and Education of Huesca, in the election of assistances for the realisation of the Act of Improvement Program of Education, with the tittle of "School Practices I, II and III from the view of the credits ECTS.One of the main aims of this project was to know the attitude of the University teachers before the school practices course, that is why we did a cuestionary to a big number of partners of Faculty Education of Huesca, Zaragoza and Teruel, with the purpose that they could transmit us their thougths and to be able to offer a solution to elaborate and develop the new plans of teacher degree, specially, refered to practicum.